Giardiasis and diarrhea in dogs: Does the microbiome matter? - Sharon Kuzi; Soha Zgairy; Barbara A. Byrne; Jan Suchodolski; Sondra C. Turjeman; So Young Park; Itamar Aroch; Mike Hong; Omry Koren; Eran Lavy (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Giardia duodenalis (Gd) causes intestinal parasitosis. The involvement of the intestinal microbiome in determining the infection's clinical phenotype is unknown. Objective Investigate the fecal microbiome features in dogs with giardiasis. Animals and Methods Cross‐sectional study, including fecal samples of kenneled dogs with Gd diagnosed by fecal Giardia antigen dot ELISA. The fecal microbial compositional characteristics and dysbiosis index (DI) were compared between diarrheic and nondiarrheic dogs. Results Fecal samples of 38 Gd‐infected dogs (diarrheic, 21; nondiarrheic, 17) were included. No differences were found in Faith's phylogenic diversity and beta diversity (weighted UniFrac distances) and in specific taxa abundances at the phylum, genus, and species levels, as well as in alpha and beta diversities between diarrheic and nondiarrheic dogs, and also when divided by sex or age. Among diarrheic dogs, alpha diversity was higher in males than in females (pairwise Kruskal‐Wallis, q = 0.01). Among males, fecal abundances of the genus Clostridium (W = 19) and Clostridium spiroforme species (W = 33) were higher in diarrheic compared to nondiarrheic dogs. In diarrheic dog fecal samples, Proteobacteria were more prevalent (W = 1), whereas Verrucomicrobia were less prevalent in dogs <1 year of age than in older dogs. The fecal sample DI of 19 diarrheic and 19 nondiarrheic dogs was similar (median, −0.2; range, −4.3 to 4.5 and median, −1.0; range, −4.3 to 5.8, respectively). Conclusions The fecal microbial composition of symptomatic and asymptomatic dogs with giardiasis is similar. Based on fecal DI, giardiasis is not characterized by prominent dysbiosis. Other host and parasite characteristics might determine the severity of giardiasis in dogs.